Microanatomy related biocidal activity at cellular resolution and bone reconstruction potential of PEG EGaIn nanocapsules - Kevin H. Mwangi; Yue Qu; Peilun Hu; Toshitatsu Nagayasu; Jia-Feng Liu; Xiumei Wang (npj Biofilms and Microbiomes)
Abstract Critical bone defects, exacerbated by infections, pose significant challenges to bone healing and homeostasis, necessitating the development of dual-functional biomimetics that combine anti-infective and reparative capabilities. The EGaIn holds promise across various disciplines, though its interactions with microbial cells require further elucidation. This investigation evaluates the antimicrobial efficacy of PEG-EGaIn nanocapsules against a spectrum of bacterial, employing electron microscopy. Constructs containing 1.5% PEG-EGaIn hinder biofilm-producing bacteria, while 3% concentrations amplify the biocidal effect. Furthermore, the nanocapsules promoted osteogenic differentiation rBMSCs, evidenced by enhanced mineralization and upregulation of key osteogenic genes. In addressing large bone defects, PEG-EGaIn-Col-Ap-lamellar and ethanolic-mediated Col-Ap-lamellar constructs serve as potential solutions for bone resorption mitigation and osteo-angiogenesis. Bone-remodeling were validated through μ-CT and histomorphometry confirming no evidence of chronic inflammation or fibrosis. In this study, PEG-EGaIn nanocapsules emerge as potent biocide and bone repair, underscoring their potential in combating antibiotic resistance and enhancing bone healing.